2006
DOI: 10.5650/jos.55.215
|View full text |Cite
|
Sign up to set email alerts
|

Anionic Gemini Surfactants: A Distinct Class of Surfactants

Abstract: Anionic gemini surfactants are a new class of surfactants that comprise of two anionic head groups and two hydrophobic tails separated by a spacer group. Anionic gemini surfactants have low cmc values and show extraordinary surface activity. These surfactants have good water solubility and their ability to form micelles and lowering surface tension characteristics are fairly good as compared to conventional anionic surfactants. These surfactants have excellent lime soap dispersing ability (LSDA) too. Because o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 38 publications
(35 reference statements)
1
21
0
1
Order By: Relevance
“…The CMCs were determined from the abrupt change in the tension trend. The CMC values in Tables 4-6 revealed that the NI product has a higher CMC value than that of surfactants GA 12 , GA 16 , and GA 18 . This result may be due to the solubility of NI being completely controlled by solvation, whereas the solubility occurs by an ionizationsolvation mixed process with GA 12 , GA 16 , and GA 18 .…”
Section: Surface Properties Of Mixtures Of Anionic Gemini and Ni Surfmentioning
confidence: 91%
See 1 more Smart Citation
“…The CMCs were determined from the abrupt change in the tension trend. The CMC values in Tables 4-6 revealed that the NI product has a higher CMC value than that of surfactants GA 12 , GA 16 , and GA 18 . This result may be due to the solubility of NI being completely controlled by solvation, whereas the solubility occurs by an ionizationsolvation mixed process with GA 12 , GA 16 , and GA 18 .…”
Section: Surface Properties Of Mixtures Of Anionic Gemini and Ni Surfmentioning
confidence: 91%
“…Tsubone et al [18][19][20][21] have studied the aqueous properties of anionic geminis of N-acylamino acids. In that investigation, some unusual interfacial behavior caused by simultaneous presence of N,N-dialkylamide and carboxylate groups in molecule, the micelle organization degree (b) of ethylene bis (sodium N-dodecanoyl-asparatate), (CH 2 ) 2 [N(COC 11 H 23 ) CH(CO 2 H)CH 2 (CO 2 H)] 2 Á 2NaOH was found to be 0.97 in aqueous solutions of NaCl (¼0.1 M) at pH 5.0.…”
Section: Anionic Gemini Surfactants Mixed With Conventional Anionic Smentioning
confidence: 99%
“…There is another special property of Gemini surfactants which is very impressive relative to other surfactants. The krafft temperature, which is also termed as critical micelle temperature that means the minimum temperature at which micelle formation takes place, is much lower than that of conventional monomeric surfactants . A surfactant having krafft temperature below room temperature is considered to be soluble and many such Gemini surfactants having hydrophilic or hydrophobic spacers have been reported with krafft temperature below 0 °C…”
Section: Classificationmentioning
confidence: 99%
“…More recently, Shukla et al [8] have reported that anionic gemini surfactants with two sulfate or sulfonate head groups have much better lime soap dispersing ability than that of single chain surfactants that have only one sulfate or sulfonate head group.…”
Section: Introductionmentioning
confidence: 98%